Các hợp chất tritecpen glycosit khung cucurbitane phân lập từ quả mướp đắng (Momordica charantia L.) (Phần 2) - Yến, Phạm Hoàng; Tuấn Anh, Hoàng Lê; Dung, Dương Thị; Minh, Châu Văn; Nhiệm, Nguyễn Xuân; Thúy Hằng, Đan Thị; Hải Yến, Dương Thị; Cúc, Nguyễn Thị; Thanh, Bùi Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2014)
From the methanol extract of the fruits of Momordica charantia L., five compounds: charantoside VIII (1), momordicoside K (2), karaviloside II (3), karaviloside V (4), and momordicoside A (5) were isolated. Their structures were determined by spectroscopcial methods and in comparison with published data. Keywords: Momordica charantia.